Um estudo sobre os processos de modalização estabelecidos pelo par é + adjetivo em artigos de opinião publicados no jornal Observatório da Imprensa. - Corbari, Alcione Tereza (2008)
This research aims at investigating the processes of modalization established by the phrase é (is) + adjective in textual excerpts from opinion articles published in the section Jornal de Debates of the online newspaper Observatório da Imprensa. Our interest in promoting an analysis in this context arises from reflections promoted by a series of researches developed by the research group Elaboração de uma gramática para graduandos (Elaboration of a grammar for undergraduate students), considering the fact that the study of linguistic modalization can contribute to the development of linguistic-discursive skills of the students as readers and text producers. During the itinerary outlined for the development of this work, we have observed that the unit é (is) + adjective represents a modalizing structure used by the text producer in order to signal his/her evaluative position regarding the message or to establish a more active interlocution with the reader aiming to convince him/her about the validity of the opinion expressed in the text. This observation led us to recognize two scopes of actuation of modalization in the structure under examination: modalizated content x interlocutor. This perspective of analysis is subsidized by some contemporary authors that study the linguistic modalization, such as Neves (2006; 1996), Koch (2002; 1997), Castilho and Castilho (1992), Parret (1988), among others. The proposal of analysis present in the bibliography contributed to evaluate the functions of the phrase é (is) + adjective and to notice that the recurrence of this structure is typical of opinion articles. The hypothesis that the linguistic choices are done on grounds of the genre finds support in authors who study the textual/discursive genre, such as Bakhtin (2003), Marcuschi (2005a; 2005b) and Matencio (2006). Melo (2003) and Rodrigues (2001) are also references for this research since they present studies on the specific characteristics of the opinion article.